New World Organisation for Animal Health (OIE) typology of public-private partnerships in support of national veterinary services - CGIAR Research Program on Livestock (2018)
The World Organisation for Animal Health (OIE) is a key institution regulating international trade of livestock and livestock products. In its endeavour to strengthen veterinary service delivery, the OIE, in consultation with experts, conducted a survey on experiences with public-private partnerships (PPPs) in 181 countries to identify case stories in the field of Veterinary Services. The CRP Livestock contributed case stories to this exercise based on tested PPP models in Kenya, Tanzania and Ethiopia.